EVALUATION OF EGGPLANT AND GILO GENOTYPES AND INTERSPECIFIC HYBRIDS AS TO ROOT-KNOT NEMATODE RESISTANCE - Jadir Borges Pinheiro; Giovani Olegario da Silva; Jhenef Gomes de Jesus; Danielle Biscaia; Raphael Augusto de Castro e Melo (Colloquium Agrariae, 2021)
In Brazil, eggplant and gilo are important for the economy of small-scale farms located mainly in the southeast states and other regions, with a significant production volume year-round in the wholesale local markets. However, these species are very susceptible to root-knot nematodes, and there are few or almost none known sources of resistance. The objective of this study was to prospect sources of resistance to root-knot nematodes in eggplant, scarlet eggplant (gilo), as well in interspecific hybrids between these species and with wild Solanum species, to be used as rootstocks. In the first experiment, in 2013, 10 eggplant accessions, a hybrid between eggplant and gilo, and a Solanum stramonifolium x eggplant hybrid, were evaluated for their reaction to Meloidogyne enterolobii. In the second, in 2016, 20 accessions of gilo were evaluated for their reaction to M. incognita, M. javanica, and M. enterolobii.. And in the third experiment, in 2017, one access and two experimental eggplant hybrids, and one Solanum scuticum x eggplant hybrid, were evaluated for their reaction to M. incognita, and M. enterolobii. All the trials were stablished in a greenhouse, and characters related to root infection were evaluated in a completely randomized design with six replications of one plant per pot, using a 1.5 L pots filled with a mixed substrate inoculated with each nematode species. It was found that all eggplant accessions were susceptible to M. incognita and M. enterolobii, however, BER 3150 presented lower susceptibility to M. incognita. The gilo genotypes CNPH 056, CNPH 070, CNPH 220, and CNPH 363 shown better response to M. incognita and M. javanica than the susceptibility pattern, the tomato 'Rutgers'. Other gilo accessions CNPH 070, CNPH 219, and CNPH 387 showed better or equivalent response than the resistant tomato 'Nemadoro' for M. enterolobii. 4- the BER EG203 x S. scuticum interspecific hybrid can be recommended as a rootstock for eggplant susceptible to M. incognita, as well the wild S. stramonifolium var. inerme species for M. enterolobii.